COLLECTING INFORMATION ON FISH LIGULIDOSE INVASION - Shcherbakova, N. S.; Krupa, K. P. (Scientific Progress & Innovations, 2019)
The purpose of this article is to highlight updated and generalized information on the ligulidose invasion of freshwater fish, namely Cyprinidae family, with emphasis on clinical manifestations of the disease, epizootology, life cycle of the invasion pathogen and its effect on food characteristics of the infested fish. In order to comprehensively cover this topic, the following methods of scientific research were used: systematic analysis of known scientific sources, empirical method (for assessing the current state of the subject under study), abstract-logical – in order to find out the basic concepts of this topic. Considering the spreading of the fishing industry on the territory of Ukraine, the problem of fish infestation with ligulidose invasion is quite urgent at present. Ligulidose invasions include ligulosis, migraine and schistocephalosis. Ligulidosis is a quite spread freshwater fish disease. Fish from the Cyprinidae family are susceptible to this group of diseases, but pike, pike perch are resistant to this invasion. The structure of the mature ligulide body corresponds to the general characteristics of the majority of cestodes, but has its own distinct differences (slightly dissected strobila, different variations in the body shape, the neck is often absent). This group of fish parasitic diseases is characterized by plerocercoids (second larval stage of the pathogen) parasitizing in the internal organs of freshwater aquatic organisms. Parasitizng of these cestodes in the internal organs causes the upsetting of their functioning, and subsequently atrophy. In addition, the process of growth and reproduction is upset. The characteristics of pathological changes are almost always the same, and represented by the exhaustion of the infested fish and their rapid death. The invasion pathogens have a wide range of hosts, which covers protozoa, fish and birds. Due to a wide range of hosts, ligulidoses spread quickly, not only on the territory of water reservoir, but also beyond its borders. Infested fish often becomes a prey to fish-eating birds, which spread this invasion over a large area. The greatest infestation intensity is detected in summer, although the infested specimens can be found at any time of the year. The infestation of fish with this invasion causes irreversible changes in aquatic organisms, which significantly affects not only the market condition of fish, but also its food characteristics. The information highlighted in this article can be used not only during scientific research, but also introduced in the process of training specialists of veterinary medicine.